2016
DOI: 10.1080/00150193.2016.1172962
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of dielectric and ferroelectric properties for (1−x)Bi0.5(Na0.8K0.2)0.5TiO3-xBaZn0.5W0.5O3lead-free piezoelectric ceramics

Abstract: The ferroelectric and piezoelectric properties of (1¡x)Bi 0.5 (Na 0.8 -K 0.2 ) 0.5 TiO 3 -xBaZn 0.5 W 0.5 O 3 ((1¡x)BNKT-xBZW) ceramics have been studied to clarify the temperature dependence of the polarizationelectric field (P-E) hysteresis and dielectric properties. Based on the temperature dependence of the dielectric constant, it was found that the depolarization temperature (T d ) shifted to lower temperatures, depending on the composition x. The crystal structure refinement of (1¡x)BNKT-xBZW ceramics wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was found that the formation of MPB in the (1 − x)BNKT-xBa 2 ZnWO 6 system allows further enhancement of ferroelectric and piezoelectric properties (d 33 = 168 pC=N at x = 0.05). 24) In addition, Sr 2 ZrTiO 6 (SZT) 25) is also known as a double perovskite structure with a space group of I4=m and shows ferroelectric behavior, although ST and SZ show the paraelectric phases. Therefore, in order to clarify the influences of ferroelectric phase SZT addition on the piezoelectric properties, (1 − x)BNKT-xSZT ceramics were synthesized and the compositional dependence of piezoelectric properties was characterized in this study.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the formation of MPB in the (1 − x)BNKT-xBa 2 ZnWO 6 system allows further enhancement of ferroelectric and piezoelectric properties (d 33 = 168 pC=N at x = 0.05). 24) In addition, Sr 2 ZrTiO 6 (SZT) 25) is also known as a double perovskite structure with a space group of I4=m and shows ferroelectric behavior, although ST and SZ show the paraelectric phases. Therefore, in order to clarify the influences of ferroelectric phase SZT addition on the piezoelectric properties, (1 − x)BNKT-xSZT ceramics were synthesized and the compositional dependence of piezoelectric properties was characterized in this study.…”
Section: Introductionmentioning
confidence: 99%